Penerapan Metode Multiple Scales untuk Masalah Galloping pada DuaSpans Kabel Transmisi - Eristia Arfi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
In this paper, galloping model is derived by using of Hooke's Law and Newton's Law. Furthermore galloping model is reduced in order to obtain a set of integro-differential equations. Analysis of system response observed with the assumption that the frequency of the external force is very close to the natural frequency of the system. Second-order expansion of analytic solutions for stationary problem from integro-differential equationsare determined using the method of multiple scales. Analysis of the behavior of the system to stability point and dynamic of solutions that depend on the parameter indicates that the initial conditions of the system affect the oscillation behavior of cable.Keywords: galloping, multiple scales, perturbation, resonace.